A STUDY ON EFFECT OF HUMOROUS ADVERTISEMENT ON CONSUMER PURCHASE DECISION - Tony, Lea; C Warriar, Malavika; Jayaraj, Malavika (International Journal of Psychosocial Rehabilitation, 2020)
In order to increase the sales of the product and face competition from similar products, the product is to be equipped to grab the attention of the consumers, persuade them to buy the product, and retain the loyalty of the customers. Advertising plays a major role in grabbing the attention of consumers. Attractive attributes used in advertisements increase the magnitude of grabbing attention. Humor as an appeal in advertisements is used by many advertisers and businessmen to boost their sales. The present study was aimed at finding the impact of humorous advertisements on the consumer purchase decision by selecting some advertisements with special reference to confectionery. Primary data was collected by employing a questionnaire that was prepared in Google Forms and sent to people for their response. The study gave a good insight about the effect of humor in advertisements and how it influenced the consumer purchase decision.